2006
DOI: 10.1300/j108v07n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Technical Efficiency in Urban Food Crop Production in Ibadan Metropolis, Oyo State, Nigeria

Abstract: This study analysed the level and the determinants of technical efficiency among urban crop farmers in Ibadan metropolis. The random sampling technique was used in selecting 85 farmers from the following three areas where urban food crop production is prominent: Ajibode, Ijokodo, and Eleyele. The data were collected through structured questionnaires and analysed using both descriptive statistics and stochastic production frontier based on the Cobb-Douglas production function. The results reveal that farmland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Methodologically, the high predictive accuracy (89% correct classification) of the discriminant model in distinguishing urban vs. rural households based on food security indicators demonstrates the value of multivariate analytical techniques for segmentation and policy analysis. Combining discriminant analysis with spatial mapping and regression approaches can provide greater nuance into drivers of food insecurity across geographical and socioeconomic divides (Omonona et al, 2019). While these findings are consistent with existing literature, the relatively small localized sample limits generalizability.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Methodologically, the high predictive accuracy (89% correct classification) of the discriminant model in distinguishing urban vs. rural households based on food security indicators demonstrates the value of multivariate analytical techniques for segmentation and policy analysis. Combining discriminant analysis with spatial mapping and regression approaches can provide greater nuance into drivers of food insecurity across geographical and socioeconomic divides (Omonona et al, 2019). While these findings are consistent with existing literature, the relatively small localized sample limits generalizability.…”
Section: Discussionsupporting
confidence: 76%
“…These results align with previous studies showing substantial disparities in food security between urban and rural areas, especially in developing countries like Nigeria. For example, Omonona et al (2019) in their analysis of national household data in Nigeria also found income, education, and household size differentiated the food security status of urban and rural households. Similarly, a study in India by Bharati et al (2022) identified income, household size, and food prices as key determinants of the urban-rural food security differential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation